Dictionary of World Biography: Fourth edition - Jones, Barry (8f667d55-46bf-4696-8daa-6edaba72f544, 2017)
Jones, Barry Owen (1932- ). Australian politician, writer and lawyer, born in Geelong. Educated at Melbourne University, he was a public servant, high school teacher, television and radio performer, university lecturer and lawyer before serving as a Labor MP in the Victorian Parliament 1972-77 and the Australian House of Representatives 1977-98. He took a leading role in reviving the Australian film industry, abolishing the death penalty in Australia, and was the first politician to raise public awareness of global warming, the 'post-industrial' society, the IT revolution, biotechnology, the rise of 'the Third Age' and the need to preserve Antarctica as a wilderness. In the Hawke Government, he was Minister for Science 1983-90, Prices and Consumer Affairs 1987, Small Business 1987-90 and Customs 1988-90. He became a member of the Executive Board of UNESCO, Paris 1991-95 and National President of the Australian Labor Party 1992-2000, 2005-06. He was Deputy Chairman of the Constitutional Convention 1998. His books include Decades of Decision 1860- (1965), Joseph II (1968), Age of Apocalypse (1975), and he edited The Penalty is Death (1968). Sleepers, Wake!: Technology and the Future of Work was published by Oxford University Press in 1982, became a bestseller and has been translated into Chinese, Japanese, Korean, Swedish and braille. The fourth edition was published in 1995. Knowledge Courage Leadership, a collection of speeches and essays, appeared in 2016. He received a DSc for his services to science in 1988 and a DLitt in 1993 for his work on information theory. Elected FTSE (1992), FAHA (1993), FAA (1996) and FASSA (2003), he is the only person to have been elected to all four Australian learned Academies. Awarded an AO in 1993, named as one of Australia's 100 'living national treasures' in 1998, he was elected a Visiting Fellow Commoner of Trinity College, Cambridge in 1999. His autobiography, A Thinking Reed, was published in 2006 and The Shock of Recognition, about music and literature, in 2016. In 2014 he received an AC for services 'as a leading intellectual in Australian public life'.